Tele-Agri-Advisory Services for Farmers: a Case Study of Kisan Call Centre in Andhra Pradesh - M. Srinivasa Rao,; V.P. Sharma, (Journal of Agricultural Extension Management, 2025)
Access to information and improved communication is a crucial requirement for sustainable· agricultural development. Information and Communication Technologies, can play a vital role by establishing a network among the researchers, extension personnel, and farmers for transfer of information. This paper examines Tele Agri Advisory services to farmers through Kisan Call Centre in Andhra Pradesh. The paper looks at call trends, level of farmers' satisfaction and implementation of solutions I recommendations offered by the Kisan Call Center, effectiveness of capacity building programmes, identifies issues, constraints and problems at various levels and gives suggestions for improvement.